Influence of Ag-Cu Binary Metal Photo Deposition Over TiO2 on its Photocatalytic Activity under Sunlight Irradiation - Deeksha (My University, 2018)
The present work demonstrates the preparation and photocatalytic activity of mono (Ag/Cu) and binary (Ag-Cu) metal deposited TiO2 photocatalysts using photo-deposition method. Various properties of catalysts were studied by DRS, PL, DLS and SEM-EDS analysis. Ag-Cu@TiO2 catalysts were found to display considerable red shift of plasmon band (460-700 nm) enhancement in a broad visible region in the absorption spectra. The effects of different amount (1-5) wt % of Ag-Cu binary metal and by varying photo-deposition time (15 - 90 min.) time on the photodegradation of Neutral red dye have been evaluated under solar light irradiation. DLS measurements showed that with increase in photo-deposition time, hydrodynamic size of various photocatalysts increase (from 72 nm of bare TiO2to 386 nm for Ag/Cu deposited TiO2) due to continuous growth of deposited Ag-Cu on TiO2 surface. From the SEM-EDS analysis it was also confirmed that during the photo-deposition of binary metal (Ag-Cu), Ag metal with higher reduction potential gets deposited first followed by Cu. Further, the photocatalytic activity of various catalysts under solar irradiations revealed that binary metal deposited Ag3- Cu3@TiO2always showed considerable increase in the photodegradation rate of dye relative to mono metal Ag/Cu-TiO2 catalysts. It has been realized that the appropriate metal NP distribution and their growth control onto TiO2 plays an important role for the effectiveness of a photocatalytic process.
Master of Science- Chemistry
Keywords: Photodeposition; Ag-Cu-TiO2; Neutral red; Photocatalytical activity